KENDALIKAN TEKANAN DARAH DAN KADAR GLUKOSA DARAH DENGAN METODE ISI PIRINGKU - abdillah, Alvin (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2024)
The elderly are at high risk of degenerative diseases such as coronary heart disease (CHD), hypertension, diabetes mellitus, and rheumatism. Hypertension and diabetes mellitus are the main risk factors for the development of heart disease and stroke that often occur in the elderly, hypertension cases are increasing in Indonesia. The purpose of this community service is to apply the results of previous research, namely to increase the elderly's concern for dietary diet to prevent hypertension and diabetes mellitus with the method of filling my plate. The results of the intervention carried out in community service after evaluation showed that most of the elderly understood and were motivated to care about the diet that must be followed. Thus, it can be concluded that this community service activity has been successfully carried out.